A History of the modern Middle East - Cleveland, William L.; Bunton, Martin P. (Philadelphia Westview Press, 2016)
"A History of the Modern Middle East examines the profound and dramatic transformation of the region in the past two centuries, from the Ottoman and Egyptian reforms, through the challenge of Western imperialism, to the impact of US foreign policies. Built around a framework of political history, while also carefully integrating social, cultural, and economic developments, this expertly crafted account by the late William Cleveland and Martin Bunton provides readers with the most comprehensive, balanced and penetrative analysis of the modern Middle East. The sixth edition has been revised to provide a thorough account of the major developments over the past four years, including the tumultuous aftermath of the Arab uprisings, the sectarian conflict in Iraq and civil war in Syria that led to the rise of ISIS, the war in Yemen, and the United States' nuclear talks with Iran. With brand-new timelines in each part, updated select bibliographies, and a wealth of online instructor resources, A History of the Modern Middle East remains the quintessential text for courses on Middle East history" -- Provided by publisher.
The development of Islamic civilization to the eighteenth century -- The rise and expansion of Islam -- The development of Islamic civilization to the fifteenth century -- The Ottoman and Safavid empires : a new imperial synthesis -- The beginnings of the era of transformation -- Forging a new synthesis : the pattern of reforms, 1789-1849 -- The Ottoman Empire and Egypt during the era of the Tanzimat -- Egypt and Iran in the late nineteenth century -- The response of Islamic society -- The era of the Young Turks and the Iranian constitutionalists -- World War I and the end of the Ottoman order -- The struggle for independence : the interwar era to the end of World War II -- Authoritarian reform in Turkey and Iran -- The Arab struggle for independence : Egypt, Iraq, and Transjordan from the interwar era to 1945 -- The Arab struggle for independence : Syria, Lebanon, and Saudi Arabia from the interwar era to 1945 -- The Palestine mandate and the birth of the state of Israel -- The independent Middle East from the end of World War II to the 1970s -- Democracy and authoritarianism : Turkey and Iran -- The Middle East in the age of Nasser : the Egyptian base -- The Middle East in the age of Nasser : the radicalization of Arab politics -- Israel and the Palestinians from 1948 to the 1970s -- The resurgence of Islam : the Middle East from the 1970s to the 1991 -- Gulf war -- The Iranian revolution and the revival of Islam -- Changing patterns of war and peace : Egypt and Lebanon in the 1970s and 1980s -- The Arabian Peninsula in the petroleum era -- The consolidation of authoritarian rule in Syria and Iraq : the regimes of Hafiz Al-Asad and Saddam Husayn -- Challenges to the existing order : the Middle East in the 1990s and 2000s -- The Palestinian Intifada and the 1991 Gulf War -- A peace so near, a peace so far : Palestinian-Israeli relations since the 1991 Gulf War -- Patterns of continuity and change in Turkey, Iran, and Lebanon -- America's troubled moment in the Middle East -- The 2011 Arab uprisings and its aftermath.
Includes bibliographical references (pages 563-587) and index.
Keywords: Middle East -- History -- 1517-.